A NOVEL INDEX OF WHOLE BODY ANTILIPOLYTIC INSULIN ACTION - Van Pelt, R.E. (2013)
Assessment of antilipolytic insulin action is important in obesity research, but extensive isotopic tracer studies are not always feasible. We evaluated whether an index of antilipolytic insulin action could be derived from readily available insulin and glycerol concentrations obtained during clamps or oral glucose tolerance tests (OGTT). We evaluated data collected from 29 subjects who had undergone a 3-stage hyperinsulinemic-euglycemic clamp (4, 8, and 40 mU/m(2)/min) with infusion of [(2)H(5)]glycerol to calculate the glycerol rate of appearance (GLY(RA)). Exponential decay curves for GLY(RA) across insulin concentrations were generated for each individual and suppression of lipolysis was calculated as the insulin concentration needed to half-maximally suppress GLY(RA) (GLY(RA) EC(50)). Areas under the curve for glycerol (GLY(AUC)) and insulin (INS(AUC)) were calculated and their products (INS(AUC)×GLY(AUC)) were calculated as an index of insulin suppression of lipolysis. The clamp index was highly correlated with GLY(RA) EC(50) (r = 0.862, p<0.001), as was an OGTT-derived index (r = 0.720, p<0.01). These findings suggest that the products of the insulin and glycerol AUC from either a clamp or an OGTT are good biomarkers of the antilipolytic action of insulin and are comparable to direct measurement by isotopic tracer methods.